Design of a Fertilizer Lifting Crane for the Canycom S25A Fertilizer Spreader Unit - Sukma, Irwan; Agus Edy Pramono (Recent in Engineering Science and Technology, 2025)
Manual lifting of fertilizer bags in plantation operations often leads to musculoskeletal disorders (MSDs) among workers due to repetitive, high-load, and ergonomically poor movements. This study aims to design an ergonomic fertilizer lifting crane integrated into the Canycom S25A Fertilizer Spreader with a 650-liter hopper to reduce physical strain and improve operational efficiency. A hydraulic crane system was designed with dual-segment arms, four lifting hooks, and two hydraulic cylinders, actuated via the unit’s PTO engine. Ergonomic evaluation was performed using the REBA assessment tools. The simulation results indicated that the maximum stress on critical components was within safe limits, with a factor of safety above 1.5. Postural analysis showed a significant improvement, where REBA scores decreased from 12 to 2 after the crane was introduced. The design offers a reliable, low-cost, and easily manufactured solution that enhances worker safety, reduces ergonomic risk, and increases productivity in fertilizer loading processes, especially in rugged field environments. The crane can be adopted in various agricultural applications where safe material handling is essential. Keywords: Ergonomics, Fertilizer Lifting Crane, Hydraulic system, REBA, Agricultural Mechanization